Regional news audiences' value perception of local news. (August 2022) - Park, Sora; Fisher, Caroline; Lee, Jee Young
Local news outlets are under threat in the digital era, and many are closing or merging with other news media due to the loss in advertising and audiences. A sustainable business model to replace traditional dependence on advertising has not yet been established. This paper examines one aspect of the business – audience payment – to explore the viability of online news subscription models in the context of local news. An online survey of 2038 news consumers in regional Australia was conducted in 2019 to examine regional news audiences' perception of the value of news as a social good and their willingness to pay for it. The results show that interest in supporting a new online local news outlet was largely determined by community-oriented values such as a sense of belonging, the ability to share the news with others, and the loss of a local news service, rather than the actual content. However, the quality of the journalism content was positively related to the audiences' willingness to pay. Trust in local news and existing local news consumption were important factors in determining both the interest in supporting local news and their willingness to pay for it. These findings highlight the tension between the social and financial value of regional news and the obstacles facing entrepreneurs hoping to address the growing news gaps in regional communities.